Trajectories of asthma and allergies from 7 years to 53 years and associations with lung function and extrapulmonary comorbidity profiles: a prospective cohort study. Issue 4 (April 2021) - Bui, Dinh S; Lodge, Caroline J; Perret, Jennifer L; Lowe, Adrian; Hamilton, Garun S; Thompson, Bruce; Giles, Graham; Tan, Daniel; Erbas, Bircan; Pirkis, Jane; Cicuttini, Flavia; Cassim, Raisa; et al.
Summary: Background: Longitudinal trajectories of asthma and allergies from childhood to adulthood might be differentially associated with lung function and chronic obstructive pulmonary disease (COPD), but associations with extrapulmonary comorbidities have not been well investigated. We aimed to assess these trajectories and examine their associations with lung function outcomes and profiles of comorbidities. Methods: In this prospective cohort study, data for asthma and related allergic conditions (ie, eczema, hay fever, and food allergy) were prospectively collected from the Tasmanian Longitudinal Health Study for participants aged 7–53 years originally recruited in Tasmania, Australia. All surviving individuals in the database with contact details were invited in the most recent follow-up (mean age 53 years). There were no exclusion criteria. With use of latent class analysis, we identified longitudinal trajectories of asthma and allergic conditions from 7–53 years, and profiles of self-reported extrapulmonary conditions recorded at 53 years. The associations between asthma and allergy trajectories and morbidity profiles and lung function at 53 years were investigated with regression models. Findings: Between Sept 3, 2012, and Nov 8, 2016, of 6128 individuals invited, 3609 (58·9%) individuals were enrolled. We identified five asthma and allergy trajectories: minimal and least asthma and allergies (n= 1767 [49·0%]); late-onset hay fever, no asthma (n=1065 [29·5%]); early-onset remitted asthma and allergies (n=236 [6·5%]); late-onset asthma and allergies (n=317 [8·8%]); and early-onset persistent asthma and allergies (n=224 [6·2%]); and four profiles of extrapulmonary morbidities: minimal or least disease (n=2206 [61·1%]); dominant mental health disorders (n=861 [23·9%]); dominant cardiovascular diseases or risks (n=424 [11·7%]); and multiple disorders (n=117 [3·2%]). The late-onset asthma and allergies trajectory was predominantly associated with the multiple disorders profile (relative risk ratio 3·3 [95% CI 1·9–5·9]), whereas the other asthma and allergy trajectories were associated only with the dominant mental health disorders profile. Both spirometrically defined and clinical COPD were most strongly associated with the early-onset persistent asthma and allergies trajectory (odds ratio [OR] 5·3 [95% CI 3·2–8·6]) and also with the late-onset asthma and allergies trajectory (OR 3·8 [2·4–6·1]). Interpretation: Distinct longitudinal trajectories of asthma and allergic disease from childhood to 53 years are associated with different profiles of extrapulmonary comorbidities and varying risk of COPD. These findings can inform a personalised approach in clinical guidelines and management focusing on treatable traits. Comorbidity profiles are a new target for early identification and intervention. Funding: National Health and Medical Research Council of Australia, EU's Horizon 2020, The University of Melbourne, Clifford Craig Medical Research Trust of Tasmania, The Victorian, Queensland & Tasmanian Asthma Foundations, The Royal Hobart Hospital, Helen MacPherson Smith Trust, and GlaxoSmithKline.